Gastroprotective Effect of Aqueous Extract of Azadirachta indica (Neem) on Ethanol Induced Gastric Lesion in Rats - Rahman, Rifayet; Khan, Ismail; Hoque, Mahbubul; Aktar, Muqbula Tasrin; Sharmin, Zinat Rehana (Bangladesh Journal of Physiology and Pharmacology, 2014)
The present study has been undertaken to find out the gastro-protective effect of aqueous extract of Azadirachta indica on ethanol induced gastric lesion in rats. To demonstrate this effect : some parameters of gastric damage -such as number of lesions, lesions length, lesions breadth, lesions area, lesions index and percent inhibition was chosen. In addition, histological features of rat stomach were also examined to confirm gastric damage and to determine the extent. The rats were provided with aqueous extract of Azadirachta indica (300mg /kg body wt) orally by gastric tube. After 12 hrs,1 ml absolute ethanol were orally administered to all groups by gastric tube. After 60 mins of administration, all rats were sacrificed. Rats pretreated with aqueous extract of Azadirachta indica (300mg /kg body wt) showed significant decrease in stomach damage both macroscopically and microscopically as compared to control. It is observed that aqueous extract of Azadirachta indica has gastroprotective effect. Therefore, aqueous extract of Azadirachta indica can be used to prevent gastric ulcer. DOI: http://dx.doi.org/10.3329/bjpp.v28i1-2.20074 Bangladesh J Physiol Pharmacol 2012; 28(1&2):10-14